KANKER KORUPSI dalam NEGARA - Balkis Soraya Tanof (Jurnal Pluralis, 2024)
It is truly ironic and tragic, In the era of reform whose mandate is to cleanse this country from corruption, collusion and nepotism (KKN), these practices have not decreased but have become more rampant. In fact, this era was born as a protest against the New Order government which was considered to be full of KKN acts. In fact, Regional Autonomy which was also born as a correction to the centralization of the New Order actually helped spread these forbidden practices to all levels of government. As a result, in this country there is almost no space that is clean from KKN.